Jornalismo, podcast e música: alternativas para a construção de discursos musicais em empresas de mídia - Rocha, Luiz Gusthavo Nunes Silva (2019)
Podcast is a broadcasting and multimedia file transmission modality, on demand, with audio as the main source of communication. With podcast growth in recent years, media companies have noticed in the modality a way to engage a hard-to-reach, but present niche audience on the internet. In Brazil, numbers of podcast reproductions have increased surpassing the millions, especially in large media companies, which shows an audience in constant growth on this platform. Given this panorama, the present study analyzes the podcast as media and phenomenon of influence in order to develop a musical journalism program for this medium. To do so, it is necessary to analyze the environment which podcasts and music journalism are included. In addition to detailing the conditions of contextualization, production and reception of podcasts, this study seeks to reflect the relations between journalism, music and technology. The present study promotes a reflection on how cultural journalism can take advantage of the podcast, a platform that allows the creation of new methods to narrate their stories with a different bias from traditional media. The methodology consists on elaborating a bibliographical research followed by interviews to try to understand if the podcast can be a useful media vehicle and in which way Brazilian press has been taking advantage of this modality, analyzing in which ways the particularities of this media of can be used successfully. The research indicates that podcasts as an internet media tool presents rapid growth and Strong connection between its listeners and producers. Finally, based on the data collected, a pilot program will be produced of a series of podcasts that try to concretize the possibility of producing alternative content in cultural journalism.